A category theory perspective on the Language of Thought: LoT is universal - Phillips, Steven (Frontiers in Psychology, 2024)
The Language of Thought (LoT) hypothesis supposes some collections of mental states and processes are symbol systems to explain language-like systematic properties of thought. Recent proponents of this hypothesis point to additional LoT-like properties in non-linguistic domains to claim that LoT remains the "best game in town" in terms of explanatory coverage. Nonetheless, LoT assumes but does not explain why/how symbolic representations connect to other (nonsymbolic) formats. The perspective presented here is supposed to bridge this gap as a duality in a category theoretical sense: (perceptual) data are projected onto a base (conceptual) space in one direction and in the opposite direction these data are referenced by that space. Accordingly, perception is dual to conception. These constructions follow from a universal mapping principle affording an explanation for why/how symbolic and non-symbolic formats are connected: as the "best" possible transformation between the two forms-so the slogan, LoT is universal. This view also sheds some light on the apparent pervasiveness of logic-like capacities across age-groups and species-these constructions constitute special kinds of categories called toposes (topoi) and every topos has an interpretation in first-order logic.